Financial Stress and Borrowing Behavior: A Literature Review - Arimbi Priadipa (Journal of Economic and Business Advancement, 2026)
This article synthesizes contemporary scholarship on financial stress and borrowing behavior through a structured interpretive literature review of Scopus-indexed studies published between 2015 and 2025. Drawing on economics, behavioral finance, and economic psychology, the review integrates empirical and theoretical evidence to explain how stress reshapes household borrowing decisions beyond rational choice assumptions. The findings indicate that financial stress operates simultaneously as a cognitive constraint, an emotional burden, and a social signal, influencing credit uptake, debt persistence, and risk tolerance. Psychological mechanisms such as decision fatigue, loss aversion, and social emotions interact with structural factors including income volatility, debt composition, and institutional context. Longitudinal and comparative studies demonstrate that borrowing under stress often reflects short-term coping rather than intertemporal optimization, with measurable consequences for mental health and subjective well-being. The synthesis further reveals persistent heterogeneity across age, socioeconomic position, and cultural settings, challenging universal policy prescriptions. Conceptually, the article advances an integrated framework linking stress dynamics to borrowing behavior across micro-level decision processes and macro-level financialization. Policy implications are discussed briefly.